Factors Associated With Short-Term Recovery Following Single-Event Multilevel Surgery for Children With Cerebral Palsy. Issue 1 (January 2023) - Lennon, Nancy; Gerry, Grace; Biermann, Isabel; Beaman, Jason; Mamula, Nicole; Gilmore, Abigail; Niiler, Tim; Shrader, M. Wade; Owens, Laura L.
Abstract : Purpose: To examine the role of multiple factors, including therapy dose, on recovery of mobility function during post–single-event multilevel surgery (SEMLS) rehabilitation in youth with cerebral palsy. Methods: Several factors expected to influence postoperative change in Gross Motor Function Measure (GMFM) were examined: age, Gross Motor Function Classification System (GMFCS) level, cognition, number of osteotomies, surgical complications, medical comorbidities, number of therapy sessions, and preoperative measures of gait, balance, and gross motor function. Results: Sixty-nine youth with cerebral palsy, GMFSC levels I-IV, who had undergone SEMLS and rehabilitation had on average 2.6 osteotomies and 89 postoperative therapy sessions. Fewer osteotomies, higher therapy dose, higher preoperative GMFM, and lower GMFM at postoperative admission were significant in determining GMFM change. Conclusions: The most relevant factors on post-SEMLS recovery were therapy dose, surgical burden, and level of gross motor function immediately before and after surgery.